The oldest Euphasmatodea (Insecta, Phasmatodea): modern morphology in an Early Cretaceous stick insect fossil from the Crato Formation of Brazil - Ghirotto, Victor M.; Crispino, Edgar B.; Chiquetto-Machado, Pedro I.; Neves, Pedro A. B. A.; Engelking, Phillip W. [UNESP]; Ribeiro, Guilherme C. (Wiley, 2022)
Stick insects (Phasmatodea) are herbivorous, mostly nocturnal insects known for their camouflage specialization, constituting a moderately diverse group with around 3400 extant described species. The overall poor and often confusing fossil record of Phasmatodea, especially regarding older taxa, has muddled the knowledge of the early evolution of the lineage and hindered reliable calibration points for ordinal-level phylogenies. The phylogenetic relationships within the order remain unresolved, but recent research sheds more light on the subject. Here we report on the oldest known fossil of Euphasmatodea, by revising the taxonomic identity of one fossil species (Eoproscopia reliquum Mendes, Vasconcelos & Oliveira) previously described as a stick grasshopper (family Proscopiidae). Based on the finding of a more complete specimen the taxon is redescribed and a new genus, Araripephasma, is erected to accommodate this species in Euphasmatodea. Araripephasma reliquum comb. nov. is a remarkably modern-looking stick insect species that provides a new minimum age for Euphasmatodea and sets a good and reliable calibration point for phylogenetic and evolutionary studies. The implications of this rare finding for the evolutionary history of Phasmatodea are discussed.
Keywords: Crato Formation; Cretaceous; Gondwana; palaeoecology; Phasmida; stick insect